A qualitative case study of Instructional Support practices in Chinese preschool classrooms. (September 2018) - Yang, Yi; Hu, Bi Ying; Yu, Shulin; Roberts, Sherron Killingsworth; Ieong, Sylvia S.L.
Highlights: Four typical Chinese preschool teachers' Instructional Support practices. Inconsistency of teachers' Instructional Support practices across settings. Variations among teachers' Instructional Support practices across quality profiles. Create more chances for children's cognitive and language development.